Recent progress in antimicrobial strategies of controlled-release nanomaterials for secondary caries - Wang, Yiyi; Du, Xushuo; Jia, Yanmin; Qin, Lu; Liu, Fei; Cai, Yingchun; Wang, Suping (Frontiers in Cellular and Infection Microbiology, 2025)
Secondary caries is a leading cause of restoration failure. Inhibiting caries through antimicrobial efficacy is essential for extending the restoration’s service life. Antimicrobial agents have been incorporated into restorative materials for decades. Based on their mechanism of antimicrobial action, these materials are classified as either releasing or non-releasing types. However, the simple release strategy is often insufficient for long-term caries prevention, as it lacks the precision, durability, and adaptability now required. This necessitates the development of next-generation systems that can provide a controlled, sustained, and targeted antimicrobial activity. To this end, this review focuses on advanced, controlled-release antimicrobial strategies, exploring the design of novel nanomaterials, their functional efficacy, and the mechanisms of their representative antimicrobial agents.